The global impact of COVID‐19 pandemic on the incidence of pediatric new‐onset type 1 diabetes and ketoacidosis: A systematic review and meta‐analysis. Issue 11 (22nd July 2022) - Rahmati, Masoud; Keshvari, Maryam; Mirnasuri, Shahrzad; Yon, Dong K.; Lee, Seung W.; Il Shin, Jae; Smith, Lee
Abstract: Viral infections may increase the risk of developing type 1 diabetes (T1D), and recent reports suggest that Coronavirus Disease 2019 (COVID‐19) might have increased the incidence of pediatric T1D and/or diabetic ketoacidosis (DKA). Therefore, this meta‐analysis aims to estimate the risk of global pediatric new‐onset T1D, DKA, and severe DKA before and after the COVID‐19 pandemic. A systematic search of MEDLINE/PubMed, CINAHL, Scopus, and EMBASE was conducted for articles published up to March 2022. A random‐effects meta‐analysis was performed to compare the relative risk of T1D and DKA among pediatric patients with T1D between the COVID‐19 pre‐pandemic and pandemic periods. We also compared glucose and HbA1c values in children who were newly diagnosed with T1D before and after the COVID‐19 pandemic. The global incidence rate of T1D in the 2019 period was 19.73 per 100 000 children and 32.39 per 100 000 in the 2020 period. Compared with pre‐COVID‐19 pandemic, the number of worldwide pediatric new‐onset T1D, DKA, and severe DKA during the first year of the COVID‐19 pandemic increased by 9.5%, 25%, and 19.5%, respectively. Compared with pre‐COVID‐19 pandemic levels, the median glucose, and HbA1c values in newly diagnosed T1D children after the COVID‐19 pandemic increased by 6.43% and 6.42%, respectively. The COVID‐19 pandemic has significantly increased the risk of global pediatric new‐onset T1D, DKA, and severe DKA. Moreover, higher glucose and HbA1c values in newly diagnosed T1D children after the COVID‐19 pandemic mandates targeted measures to raise public and physician awareness.